Konstruksi Citra Perempuan Dalam Iklan Kecap ABC “Perasan Pertama Lebih Kaya Rasa” - Laksmi Indraswari, Ida Ayu Pradnyana; Pascarani, Ni Nyoman Dewi; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium; Vol 1 No 1 (2019), 2019)
ABSTRACT Advertisement has a major role in supporting the marketing success of a product and service. In the case of binding to the public's attractiveness, the female figure is often used as a symbol to display the visual form of the audience. The image of women formed generally is a combination of sex objects, mothers or wives. But now with the times, advertisement has also undergone a change, as is the Kecap ABC “Perasan Pertama Lebih Kaya Rasa”. Through qualitative research using Roland Barthes's semiotic analysis method, the results show that the construction of the image of women in Kecap ABC “Perasan Pertama Lebih Kaya Rasa” is the image of the Pinggan, the image of the Pillar and the image of the Pigura. Women are now able to do male work and implied the dual role of women and the existence of gender equality. Keywords: Gender Equality, Gender Roles, Television Advertising, Women's Image